Metode Pendidikan Agama pada Anak Balita suatu Pendekatan Psikologis - Siti Aminah (LPPM Institut Nasional Laa Roiba Bogor, 2019)
The purpose of this study is to find out effective and efficient methods of religious education ineducating children under five using a psychological approach. This research uses descriptive analyticmethod through literature study. Data collection techniques use a variety of literature related to thediscussion, as well as the Koran and hadith. Data analysis is content analysis trying to give a significantmeaning to the analysis, explaining the description patterns, and looking for relationships between thedimensions of the description.. The results showed that: (1) Method is one of the educational componentsused in fostering and educating children. Educators need to choose the method of education in accordancewith the level of development of religious life comprehension in children, (2) The development of childrenis the development of the functions of the soul integrally, related to one another. Each level of developmentrequires guidance and appropriate leadership according to their needs for life preparation in the future,(3) Toddler age is a sensitive period in physical and spiritual growth and development. Therefore it isnecessary to prepare a religious environment so that the soul of religion is embedded in him that can beused as a basic capital of faith in his adult life, (4) The effectiveness of a method is very dependent on thepersonal educator and the level of development and needs of children.Keywords: Educational Methods, Toddler, Psychological